Produksi Film Pendek Edukasi Dengan Teknik P.O.V Menggunakan SnorriCam - Calvyn Soputra (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2021)
Anxiety is common, but long-standing and excessive reaction can lead to psychological disorders such as Generalized Anxiety Disorder. GAD Sufferers can feel fear and anxiety about things that are not specific object or situations. According to the ministry of Health, symptoms of excessive anxiety are felt by the age of 15 years and over, especially for students. To raise public awareness was made a short film titeled “In My Mind: Generalized Anxiety Disorder”. In the production prosses has 4 stages namely, data analysis, pre-production, production, post-production. In some scenes use the P.O.V technique using SnorriCam as a shooting tool to emphasize the emotions of the main character. The P.O.V echnique using SnorriCam is considered successful in conveying the main character emotions better and easily understood by the audience. In the production of this film there are 19 scene with a duration of approximately 15 minutes. The film is supported by various film support elements, including movie poster, brochure, DVD cover design, key chain, mugs, pins, tote bags, t-shirt, movie trailer, and x-banner.